Tourism and transformation: negotiating metaphors, experiencing change - Sampaio, S. (2014)
The article introduces this special issue on tourism and transformation. After offering a brief review of the place and significance of ‘transformation’ in social sciences studies of tourism – from ‘impact studies’ to ethnographies of tourists and, more recently, ‘tourist media studies’ – we propose to take one step further and focus our attention on the performativity and reflexivity of ‘transformation’. Our main argument is that much may be gained analytically by considering how notions and experiences of transformation are addressed, negotiated and purposefully deployed in tourism contexts. We conclude with an outline of each of the contributions to this special issue, stressing that the collection re-opens the issue of transformation in tourism and provides new insights into how experiences-turned metaphors and metaphors-turnedexperiences influence both the travel experience and the development of theory.